2020
DOI: 10.4018/978-1-7998-0210-5.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication for Viral Hepatitis Management Among Migrants

Abstract: The burden of viral hepatitis is high with huge mortality and morbidity on human population. The increasing migration of people from areas highly prevalent of viral hepatitis poses a unique threat to the healthcare systems of the host nations. The deficient universal standards for screening, vaccination, and treatment of viral hepatitis have therefore made the burden of chronic liver disease and hepatocellular carcinoma to increase among migrant populations globally. This study examines the role of risk commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This study revealed that the inadequate attention given to hepatitis B communication strategies and management by the government is as a result of little or no response of international aid and donor agencies towards hepatitis. The government approach as revealed in this study has been noted by previous studies (Adesina et al, 2020;Ejiofor et al, 2010;Emechebe et al, 2009;FitzSimons et al, 2016;Nwokediuko, 2011). This explains the high mortality and morbidity rate from diseases in Nigeria.…”
Section: Discussionsupporting
confidence: 72%
“…This study revealed that the inadequate attention given to hepatitis B communication strategies and management by the government is as a result of little or no response of international aid and donor agencies towards hepatitis. The government approach as revealed in this study has been noted by previous studies (Adesina et al, 2020;Ejiofor et al, 2010;Emechebe et al, 2009;FitzSimons et al, 2016;Nwokediuko, 2011). This explains the high mortality and morbidity rate from diseases in Nigeria.…”
Section: Discussionsupporting
confidence: 72%
“…In the assertion of Nutbeam [ 20 ], health communication is, therefore, an essential approach to managing public health issues. Increasing health literacy levels among the population to understand and apply information relating to health issues and achieving a substantial impact on health behaviours [ 7 , 21 23 ] are critical functions of health communication.…”
Section: Introductionmentioning
confidence: 99%
“…Studies likewise affirm that these tools are repositories of viral hepatitis and they have been accounted for as a source of VH transmission in a VH infection outbreak [12]. Previous studies show that tattooing and bodypenetrating are risk factors for VH transmission, and in the previous twenty years, it has been attested that needle therapy is an autonomous risk factor for VH infection [12]- [14]. It is likewise notable that VH could be communicated through sex and consequently perilous sexual practices are a risk factor for VH infection.…”
Section: Discussionmentioning
confidence: 89%